Enhancing Family Resilience: Implementation of Counseling by PUSPAGA in Surabaya - Hayyu Nur Larasati; Vania Ardelia (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Family resilience is an aspect that can improve well-being and attachment between family members. Of course, every family cannot be separated from conflict, and how to resolve conflict is important so that there is no family division. One way to strengthen family resilience is through counseling. To support this, the Surabaya city government developed PUSPAGA (Family Learning Center) as a form of policy to provide free counseling services for Surabaya residents. However, until now, the effectiveness of this service program has not been examined further. Therefore, this study aims to explore the effectiveness of the counseling service program provided at PUSPAGA. The research used a qualitative case study design with observation and interview data collection techniques. Interview data were collected from three clients and one officer at PUSPAGA. Data were analyzed using data triangulation through observation, interviews, and literature review. The results found that the counseling provided at PUSPAGA was considered satisfactory by clients and was able to support family resilience in dealing with conflict. This research is expected to provide a more in-depth picture of the importance of conflict in family resilience, especially in the services provided by PUSPAGA.